Transition radiation of the modulated electron stream in the strongly inhomogeneous magnetized plasma - Anisimov, I.O.; Nychyporuk, T.V. (Вопросы атомной науки и техники, 2002)
Transition radiation of the modulated electron stream moving along the concentration gradient of the cold planarly stratified strongly inhomogeneous plasma is calculated for the case of strong external magnetic field parallel to the concentration gradient.